Influencia de la televisión en el rendimiento académico de los niños de 5 años de la Institución Educativa Inicial Nº288 - de la provincia de Rioja en el año 2003 - Cerna Coronel, Luzmila (2004)
Since television came as part of everyday life of man in society he has managed to change their lives significantly has even entered each household where he has monopolized the attention especially children making up our time one their favorite entertainment so much that has come to strongly interfere with school activities affecting learning in different ways. Esla worrying situation led to consider the problem of the influence of television on academic achievement guide us to show that if an excess poor academic performance would through a correlational design: contrast the two variables involved in the study an equivalent population of 110 students from 5 years old. Procedurally was necessary first to qualitatively determine the frequency of use of the children's television that is what is determined that children tend to watch television time, that with respect to the first variable. The second variable was measured using only the epithets of the minutes of school pupils as designed proceeded to the correlation which showed the absence of it. The analytical process of the results showed that students actually make excessive use of television in the study population however is not sufficient cause to cause a decline in academic performance of students, since all conformantes students in the sample, They exhibit satisfactory schooling and passing situation. It is believed that the information system of school evaluation is handled currently does not reflect specific qualitative components, so no negative indicators are noticed as it can produce television in shaping the child and can pass unnoticed serious situations of negative learning this means inserted into the personality of the school. On the other hand it is necessary for parents to be more careful in controlling effects of television on children, to prevent future social ills. The importance of the work done is very important because it allows to define some facile postures consider television as a powerful interferer, without being questioned and tested these variables.